The Strategic Role of Biotechnology in Aquaculture: Integrating Upstream and Downstream Processes for Sustainable Fish Production - Aisyah; Andriani, Yuli (Journal of Fish Health, 2025)
Aquaculture has become an essential contributor to global food security, yet its rapid expansion presents significant challenges, including disease outbreaks, environmental degradation, and feed inefficiency. Biotechnology offers transformative solutions across the entire aquaculture value chain ranging from upstream breeding and health management to downstream processing and product safety. This review examines the strategic role of biotechnological innovations in enhancing sustainability, productivity, and resilience in aquaculture systems. Key upstream applications include selective breeding, marker-assisted selection (MAS), recombinant DNA vaccines, and probiotic-supplemented feeds, all of which have demonstrated substantial improvements in growth rates, feed conversion, and disease resistance. In midstream operations, molecular diagnostics (e.g., qPCR, LAMP) and enzyme-assisted processing technologies ensure product quality and safety. Downstream, innovations such as biosensor-based cold chain monitoring, value-added probiotic fish products, and DNA-based traceability cater to evolving consumer demands and regulatory standards. The integration of emerging tools—such as CRISPR/Cas9 gene editing, RNA interference, metagenomics, and nanotechnology—further strengthens the aquaculture sector's capacity to adapt to climate stress and global market needs. Overall, this review highlights biotechnology as a pivotal enabler of sustainable intensification in aquaculture and underscores the need for policy support, technological accessibility, and interdisciplinary collaboration to realize its full potential.